2020
DOI: 10.26434/chemrxiv.13265312
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Titanium-interlayer Mediated Hydroxyapatite Coating on Polyetheretherketone: A Prospective Study in Patients with Single-level Cervical Degenerative Disc Disease

et al.

Abstract: Currently, there are limited reports regarding investigation of the biological properties of polyetheretherketone (PEEK) coated with titanium (Ti) and hydroxyapatite (HA) in human. The objective of this study is to evaluate the in vivo response of the PEEK cages coated with Ti and HA versus uncoated PEEK cages after anterior cervical discectomy and fusion (ACDF) in patients with single-level cervical degenerative disc disease (CDDD). Twenty-four patients with PEEK cages coated with Ti and HA (PEEK/Ti/HA group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…All surgeries for all patients in this study were accomplished by the same surgeon and by following standard surgical procedures [4,16]. All procedures were performed in supine position and through a transverse skin incision on the right side of the neck.…”
Section: Methodsmentioning
confidence: 99%
“…All surgeries for all patients in this study were accomplished by the same surgeon and by following standard surgical procedures [4,16]. All procedures were performed in supine position and through a transverse skin incision on the right side of the neck.…”
Section: Methodsmentioning
confidence: 99%
“…Henceforward, PEEK has received increasing interest in the biomedical field owning to its outstanding performances in mechanical strength [12], thermal/chemical stability [13], and nontoxicity [14]. Nowadays, PEEK is of great interest as an alternative material to the commonly used Ti and its alloys [10], and are seeing increasing applications in biomedical devices such as intervertebral fusion device [15], fixation devices [16], skull [17], knee joints [18], hip joints [19], dental implants [20], etc. Fig 1 and Table 1 provide a brief summary on the recent applications of PEEK in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Intervertebral fusion device, Reproduced with permission. [15] Copy right 2020 Springer Nature; Fixation devices, Reproduced with permission. [16] Copy right 2020 Elsevier; skull repair, Reproduced with permission.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Several in vivo studies have shown an increase in bone ingrowth for implants coated with HA or CaP. 24,25 However, there are also concerns with plasma-sprayed coatings. Some studies have shown there is a risk of delamination of the coating from the surface of the implant, resulting in clinical implant failure due to the micromotion caused by debris and loose particles.…”
Section: Introductionmentioning
confidence: 99%
“…The implant surface can also be chemically altered by applying calcium phosphate (CaP) and hydroxyapatite (HA) coatings, which allow for a chemical bonding between the implant and bone surfaces due to the chemical similarities of bone and CaP and HA 22,23 . Several in vivo studies have shown an increase in bone ingrowth for implants coated with HA or CaP 24,25 . However, there are also concerns with plasma‐sprayed coatings.…”
Section: Introductionmentioning
confidence: 99%